Shariah kodifikasi hukum Islam oleh Abdurrahman J Doi ; penerjemah, H. Basri Iba Asghary, H. Wadi Masturi - ABDUR RAHMAN, J DOI; Asghary, H. Basri Iba; Masturi, H. Wadi (Rineka Cipta, 1993)
xiv, 175 hlm. 21 cm.